Global applications of the Internet of things in digital marketing - Naim, Arshi 1976-; Devi, V. Ajantha 1981- (Advances in marketing, customer relationship management, and E-services (AMCRMES), 2023)
In today's modern world, it is essential for businesses to remain competitive and up to date on the latest technology that can support their processes. The use of the internet of things (IoT) in marketing, particularly in digital marketing, is an evolving field that requires further study to better understand its potential. Global Applications of the Internet of Things in Digital Marketing focuses on the applications of IoT in customizing content and developin